2012
DOI: 10.1007/s12010-012-9717-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microaerobic Fermentation in Preprocessing Fibrous Lignocellulosic Materials

Abstract: Amending soil with organic matter is common in agricultural and logging practices. Such amendments have benefits to soil fertility and crop yields. These benefits may be increased if material is preprocessed before introduction into soil. We analyzed the efficiency of microaerobic fermentation (MF), also referred to as Bokashi, in preprocessing fibrous lignocellulosic (FLC) organic materials using varying produce amendments and leachate treatments. Adding produce amendments increased leachate production and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This study showed that lactic acid fermentation combined with thermophilic composting during a two year run experiment might contribute to an overall shorter composting period (33 days) compared to the usual aerobic composting (45-180 days) (Wang Lactic acid fermentation of human excreta for agricultural application 62 et Fornes et al, 2012). Thermophilic temperatures in the current study were achieved during the second-fifth day without any manual turning with passive aeration only, such type of compost being described as of the "micro-aerobic type" (Wang et al, 2007;Green and Popa, 2011;Alattar et al, 2012), however to prove this determination of the oxygen concentration in the compost pile is required.…”
Section: Combined Lactic Acid Fermentation and Thermophilic Compostingmentioning
confidence: 72%
“…This study showed that lactic acid fermentation combined with thermophilic composting during a two year run experiment might contribute to an overall shorter composting period (33 days) compared to the usual aerobic composting (45-180 days) (Wang Lactic acid fermentation of human excreta for agricultural application 62 et Fornes et al, 2012). Thermophilic temperatures in the current study were achieved during the second-fifth day without any manual turning with passive aeration only, such type of compost being described as of the "micro-aerobic type" (Wang et al, 2007;Green and Popa, 2011;Alattar et al, 2012), however to prove this determination of the oxygen concentration in the compost pile is required.…”
Section: Combined Lactic Acid Fermentation and Thermophilic Compostingmentioning
confidence: 72%
“…During fermentation, a compost leachate rich in carboxylic acids, alcohols and amines, is produced and should be continuously drained. Liquid, in the form of water or leachate pre-treated by aeration, must be added to the system periodically to maintain moisture levels, which also enhances the extraction of more nutrients from the solid phase into the liquid phase (Alattar et al, 2012). MF processing is unlike conventional composting, where most nutrients remain locked in the solid phase and salinity, especially sodium and chloride (an undesirable portion of post-consumer food and manure composts), cannot be decreased (Tester and Parr, 1982;Turan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Conditions inside the fermenter are microaerobic, moist, and should evolve toward acidic (pH approximately 3.4-3.8) due to buildup of organic acids (mainly lactic and acetic). (Alattar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ecology of these microorganisms is very dependent on the chemical, physical and biological composition of the soil, but it has been reported that such microbes play a relevant role in the natural or induced suppression of the soil, a rather complex phenomenon that results in reduction of the deleterious effects of various phytopathogenic microorganisms [12]. In the preparation of a bokashi, the microorganisms act on the organic matter and ferment it [13], with the consequent production of organic acids, vitamins, enzymes, amino acids and polysaccharides important for plant growth. However, the role of bokashi controling plant disease still unclear.…”
Section: Introductionmentioning
confidence: 99%